2021
DOI: 10.1186/s40164-020-00193-z
|View full text |Cite
|
Sign up to set email alerts
|

The degree of microsatellite instability predicts response to PD-1 blockade immunotherapy in mismatch repair-deficient/microsatellite instability-high colorectal cancers

Abstract: The development of programmed cell death-1 inhibitor (PD-1) has shed light on the treatment of tumors with deficiencies in DNA mismatch repair system or microsatellite instability (dMMR/MSI). However, predicting the subset in this group that will benefit from PD-1 blockade remains a challenge. In this study, we aimed to investigate the relationship between the degree of microsatellite instability and the responses to anti-PD-1 immunotherapy. 33 patients with colorectal adenocarcinoma who had a known MSI status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…DNA mismatch repair (MMR), which is vital for the maintenance of genomic stability, has been identified to play critical roles in the pathogenesis of AML [ 151 ]. Recent findings have suggested that a high degree of microsatellite instability can predict patient response to PD-1 blocker in colorectal cancer [ 152 ]. IFN-γ is secreted by activated CD8 + T cells to inhibit tumor cell proliferation, while it also upregulates PD-L1 on these cells [ 153 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…DNA mismatch repair (MMR), which is vital for the maintenance of genomic stability, has been identified to play critical roles in the pathogenesis of AML [ 151 ]. Recent findings have suggested that a high degree of microsatellite instability can predict patient response to PD-1 blocker in colorectal cancer [ 152 ]. IFN-γ is secreted by activated CD8 + T cells to inhibit tumor cell proliferation, while it also upregulates PD-L1 on these cells [ 153 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…When the association between the two qualitative variables was evaluated, there was a statistically significant relationship based on the results of a chi-squared test. This relationship shows how cases with a loss of expression of the repair genes present a greater response, primarily at the expense of patients with partial responses [ 23 ]. These observations were not influenced by other factors such as age, sex, or histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the microsatellite instability status was correlated with the tumour PD-L1 expression score in pre-neoCRT biopsies. The possible mechanism resulted from the increased tumors immunogenicity and lymphocytic infltration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%